The importance of SD goals indicators 7, 8, 9 and 12 in the industry development by using multi criteria and decision making method - Osmani, Fisnik (Array, 2020)
Sustainable Development and Decision Making are just two of the many processes that affect the industry sector. SDG7, SDG8, SDG9 and SDG 12 as four goals of sustainable development show the indicators we have to deal with, given that the energy, industry, economy and production are closely connected. This research focuses on promoting sustainable development in the industry, by testing very important indicators using the MCDM method. Our analysis was carried out with the help of a multi-criteria decision-making method - the Hierarchical Analytical Process. Through this method, we have identified specific areas that need improvement, the importance of the indicators separately, ranking so by their importance and impact in the industry, economy and production.